Employee Engagement Memediasi Quality Of Work Life Dan Perceived Organizational Support Terhadap Organizational Citizenship Behavior - Valentina, Rida Dwi; Muhdiyanto, Muhdiyanto; Suwarto, Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2022)
The purpose of the study was to obtain mediation results of employee engagement on the effect of quality of work life and perceived organizational support on organizational citizenship behavior. This research was conducted using social exchange theory. There are 4 (four) hypotheses in this study. The population used is PDAM Magelang City employees. The sampling technique was purposive sampling. The criteria used are employees working at least 2 (two) years. The number of samples is 70 respondents. The analytical tool used is SEM with Warp-PLS software. The results show that quality of work life and perceived organizational support have a direct influence on organizational citizenship behavior and employee engagement. Quality of work life and Perceived organizational support have an indirect influence on organizational citizenship behavior through employee engagement.